Pure partial trisomy for long arm of chromosome 9. Issue 3 (June 1976) - Faed, M; Robertson, J; Brown, S; Smail, P J; Muckhart, R D
Abstract : A case of a 4-year-old boy with trisomy of the long arm of chromosome 9 is described (46, XY, der (9), t (9;9) (q32;q12)). The trisomy is probably the result of a translocation of the long arm of the chromosome from one homologue to the other in a parental gonad. The clinical features of the child which include severe developmental retardation, bird-like facies, tapered fingers, and flexion contractures of the legs are similar to those of the few cases described of trisomy of the whole chromosome.